Chairing Change: What You Should Know About University Consolidations - Laura Palmer (Academic Chairpersons Conference Proceedings, 2018)
University consolidations present department chairs with unique challenges. This session will examine, from a department chair perspective, key points to consider and posit best practices to help ensure a smooth transition. With examples from a recent consolidation, this presentation will help chairs frame their role during this critical time.
Keywords: consolidations; mergers; change management; acquisitions; takeovers